Real time thermal monitoring of lithium batteries with fiber sensors and thermocouples: A comparative study. (December 2017) - Nascimento, Micael; Ferreira, Marta S.; Pinto, João L.
Highlights: Thermal monitoring in real time of lithium batteries with FBGs and TCs. Comparative responses of both types of sensors under different operating conditions. Lower 28.2% rise time was detected by the FBGs when compared to TCs. The temperature gradient profile in the battery surface depends on discharge C-rate. FBGs can be useful for failure detection and optimized BMS under abuse conditions. Abstract: This work shows a comparative study between the thermocouples and fiber sensors response for the monitoring of temperature variations occurring in three different locations of a lithium battery. The battery is submitted to constant current charge and different discharge rates, under normal and abusive operating conditions. For this specific application, the results show that the fiber Bragg grating sensors have better resolution and a rise time 28.2% lower than the K‐type thermocouples, making them a better choice for the real time monitoring of the battery surface temperature as well as a useful tool for failure detection and an optimized management in batteries.